Opposite Interplay between PPAR Gamma and Canonical Wnt/Beta-Catenin Pathway in Amyotrophic Lateral Sclerosis - Lecarpentier, Yves; Vallée, Alexandre (Frontiers in Neurology, 2016)
The opposite interplay between peroxisome proliferator-activated receptor gamma (PPAR gamma) and Wnt/beta-catenin signaling has led to the categorization of neurodegenerative diseases (NDs) as either NDs in which PPAR gamma is downregulated whereas the canonical Wnt/beta-catenin pathway is upregulated (amyotrophic lateral sclerosis (ALS), Parkinson's disease, Huntington's disease, multiple sclerosis, Friedreich's ataxia) or NDs in which PPAR gamma is upregulated while the canonical Wnt-beta-catenin signaling is downregulated (bipolar disorder, schizophrenia, Alzheimer's disease). ALS, a common adult-onset debilitating ND, is characterized by a chronic and progressive degeneration of upper and lower motor neurons resulting in muscular atrophy, paralysis and ultimately death. The intent of this review is to provide an analysis of the integration of these two opposed systems, i.e., canonical Wnt/beta-catenin and PPAR gamma, in ALS. Understanding this integration may aid in the development of novel ALS therapies. Although the canonical Wnt/beta-catenin pathway is upregulated in ALS, riluzole, an enhancer of the canonical Wnt signaling, is classically prescribed in this disease in humans. However, studies carried out on ALS transgenic mice have shown beneficial effects after treatment by PPAR gamma agonists partly due to their anti-inflammatory effects.